Multimodal interaction with BIM data in immersive virtual reality - Alves, L.; Eloy, S.; Dias, J.; Costa, T.; Gaspar, F. (3rd BIM International Conference BIC 2015, 2015)
In this paper, we combine the potential brought by BIM standards to AEC processes, with the recent trends and results taken from human-computer interaction (HCI). As a result, our system supports the visualization and interaction with 3D BIM models of buildings, at full scale in an immersive virtual reality (VR) environment, using natural and multimodal HCI, namely, combining gesture with speech. We´ve carried usability and user satisfaction evaluation with a panel of architects, engineers and architect students and our research shows that such an environment allows a deeper understanding of the work throughout the design process and improve the communication between AEC specialties, during design briefs. We have concluded also, that our technology offers great benefits during all the stages of design, from the initial phase of conceptual design until the detailed stages up to the construction work. The practical experimentation of our in-house developed system, was possible by taking advantage of the virtual reality facilities of ISCTE-IUL, namely, its PocketCAVE lab.